Православні муровані храми міжвоєнних Чернівців як об’єкти історико-архітектурної cпадщини румунського періоду - Чучко, Михайло Костянтинович; Chuchko, Mykhailo (Археологія Буковини: здобутки та перспективи: Тези доповідей VІ міжнародного наукового семінару (м. Чернівці, 16 грудня 2022 р.)., 2022)
In the 30s of the XX century. a number of new brick buildings appeared in Chernivtsi Orthodox churches, the projects of which were developed by architects and engineers organized by the Bukovyna Metropolis of the Architectural Office. In all brick Orthodox churches of Chernivtsi, built in the Romanian period, was embodied historical "neo-Romanian" style, the most characteristic for architecture of the Romanian kingdom in the interwar period.
Orthodox brick churches of the interwar period Chernivtsi as objects of historical and architectural heritage Romanian period
ЧНУ
Keywords: Чернівці, Буковина, Румунія, Буковинська митрополія, православні церкви, архітектура, міжвоєнний період; Chernivtsi, Bukovina, Romania, Bukovina Metropolitanate, Orthodox churches, architecture, interwar period